Enhanced subglacial discharge from Antarctica during meltwater pulse 1A - Li, Tao; Robinson, Laura F.; MacGilchrist, Graeme; Chen, Tianyu; Stewart, Joseph A.; Burke, Andrea; Wang, Maoyu; Chen, Jun; Rae, James W. B. (Nature Communications, 2023)
This research is funded by the National Natural Science Foundation of China (41991325, T.L. and T.C.), the Strategic Priority Research Program of Chinese Academy of Sciences (XDB40010200, T.L. and T.C.), the European Research Council, the Natural Environmental Research Council, the U.S. National Science Foundation (PLR-1425989, G.A.M), the UK Research and Innovation (MR/W013835/1, G.A.M), the National Oceanic and Atmospheric Administration (NOAA) Ocean Exploration Trust, and the State Key Laboratory of Palaeobiology and Stratigraphy. Subglacial discharge from the Antarctic Ice Sheet (AIS) likely played a crucial role in the loss of the ice sheet and the subsequent rise in sea level during the last deglaciation. However, no direct proxy is currently available to document subglacial discharge from the AIS, which leaves significant gaps in our understanding of the complex interactions between subglacial discharge and ice-sheet stability. Here we present deep-sea coral 234U/238U records from the Drake Passage in the Southern Ocean to track subglacial discharge from the AIS. Our findings reveal distinctively higher seawater 234U/238U values from 15,400 to 14,000 years ago, corresponding to the period of the highest iceberg-rafted debris flux and the occurrence of the meltwater pulse 1A event. This correlation suggests a causal link between enhanced subglacial discharge, synchronous retreat of the AIS, and the rapid rise in sea levels. The enhanced subglacial discharge and subsequent AIS retreat appear to have been preconditioned by a stronger and warmer Circumpolar Deep Water, thus underscoring the critical role of oceanic heat in driving major ice-sheet retreat. Peer reviewed